Analisis Rasio Keuangan Pada Laporan Keuangan PT Mayora Indah Tbk - Arundati, Alodia Apta; Sari, Anisa Rahma; Subhi, Muhammad Alwi; Najib, M Thoha Ainun (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
The purpose of this study is to assess the capacity of Pt Mayora Indah Tbk in managing its company's finances from 2022 to 2023. One approach to financial statement analysis is the technique used to evaluate financial performance. The method used is quantitative descriptive, with secondary data sources. The method used in analyzing is quantitative descriptive. The ratios used in analyzing financial statements are liquidity ratio, solvency ratio, activity ratio and profitability ratio. The financial condition of PT. Mayora Indah Tbk for the 2022-2023 period is seen from its poor liquidity ratio. Due to the liquidity of PT. Mayora Indah Tbk is positioned far below industry standards. Based on the solvency ratio, it was found that the company's debt is still too high because it is positioned above industry standards. However, the Company is also able to provide its own capital because the capital obtained from creditors is positioned below industry standards. In addition, the interest that can be paid by the company can be declared good because it exceeds industry standards and the company in obtaining long-term debt. The company's activity ratio is in poor condition because the average value of working capital turnover, fixed asset turnover, and total asset turnover are considered to be below industry standards. The profitability ratio is still considered substandard because the net profit margin, return on investment, and return on equity are still below industry standards